M. tuberculosis CRISPR/Cas proteins are secreted virulence factors that trigger cellular immune responses. Issue 1 (31st December 2021) - Jiao, Jianjian; Zheng, Nan; Wei, Wenjing; Fleming, Joy; Wang, Xingyun; Li, Zihui; Zhang, Lili; Liu, Yi; Zhang, Zongde; Shen, Adong; Chuanyou, Li; Bi, Lijun; et al.
ABSTRACT: The role of prokaryotic CRISPR/Cas system proteins as a defensive shield against invasive nucleic acids has been studied extensively. Non-canonical roles in pathogenesis involving intracellular targeting of certain virulence-associated endogenous mRNA have also been reported for some Type I and Type II CRISPR/Cas proteins, but no such roles have yet been established for Type III system proteins. Here, we demonstrate that M. tuberculosis (Type III-A system) CRISPR/Cas proteins Csm1, Csm3, Csm5, Csm6, and Cas6 are secreted and induce host immune responses. Using cell and animal experiments, we show that Cas6, in particular, provokes IFN-γ release from PBMCs from active tuberculosis (TB) patients, and its deletion markedly attenuates virulence in a murine M. tuberculosis challenge model. Recombinant MTBCas6 induces apoptosis of macrophages and lung fibroblasts, and interacts with the surface of cells in a caspase and TLR-2 independent manner. Transcriptomic and signal pathway studies using THP-1 macrophages stimulated with MTBCas6 indicated that MTBCas6 upregulates expression of genes associated with the NF-κB pathway leading to higher levels of IL-6, IL-1β, and TNF-α release, cytokines known to activate immune system cells in response to M. tuberculosis infection. Our findings suggest that, in addition to their intracellular shielding role, M. tuberculosis CRISPR/Cas proteins have non-canonical extracellular roles, functioning like a virulent sword, and activating host immune responses.